Pengaruh Biochar dan Pupuk Organik Cair dari Air Cucian Beras Terhadap Pertumbuhan dan Produksi Selada - Deno Okalia; Tri Nopsagiarti; Gusti Marlina (Universitas Pattimura, 2021)
Growing vegetable crops such as lettuce, on Ultisol soil has several obstacles, such as insufficient organic matter and nutrients in the soil. The provision of biochar and POC leri or organic fertilizer from rice washing liquid is expected to be a long-term and sustainable solution. This study was intended to test the addition of biochar to the growing media and the application of leri on lettuce cultivation. This study used a factorial Randomized Block Design (RAK) method. The first factor was the application of biochar to the planting medium (M), which consisted of M1: Ultisol without biochar and M2: Ultisol + 30 g biochar. The second factor was the administration of liquid organic fertilizer (LOF) leri (P), with 5 treatments consisting of P0: without giving LOF leri, P1: giving LOF leri without fermentation once a week, P2: giving LOF leri without fermentation twice a week, P3: giving fermented LOF leri once a week, P4: giving fermented LOF leri twice a week. The results of this study were tested statistically by analysis of variance, with the F test; if there was a significant difference, it was continued with the BNJ test (Honest Significant Difference) at a 0.05 level. The results showed that the best treatment of LOF leri in increasing lettuce growth and yield was 25% fermented LOF leri given 2 times a week, at 250 mL per lettuce plant. As a single treatment the best growing media was M2 (Ultisol soil + 30 g of biochar) with a plant height of 25.80 cm and the leaf number of 12.83; whereas the best LOF leri treatment was P4 (fermented LOF leri given twice a week), with a plant height of 30.27 cm and leaf number of 14.42. Based on whole plant fresh weight, the best treatment was the M2P4 (Ultisol + biochar growing medium and fermented LOF leri given week), which was 185.99 g per plant. Keywords: household waste, lettuce, POC leri, rice washing liquid ABSTRAK Melakukan budidaya tanaman sayuran, seperti selada, pada tanah Ultisol memiliki beberapa kendala, seperti kurangnya bahan organik dan unsur hara pada tanah tersebut. Pemberian biochar dan POC leri atau pupuk organik dari cairan cucian beras diharapkan dapat menjadi solusi yang bersifat jangka panjang dan berkelanjutan. Penelitian ini dimaksudkan untuk menguji penambahan biochar pada media tanam dan pemberian leri pada budidaya selada. Penelitian ini menggunakan metode Rancangan Acak Kelompok (RAK) faktorial. Faktor pertama adalah pemberian biochar pada media tanam (M), yang terdiri dari M1: Ultisol tanpa biochar dan M2: Ultisol + 30 g biochar. Faktor kedua adalah pemberian pupuk organic cair (POC) leri (P), dengan sebanyak 5 perlakuan yang terdiri dari adalah P0: tanpa pemberian POC leri, P1: pemberian POC leri tanpa fermentasi 1 kali seminggu, P2: pemberian POC leri tanpa fermentasi 2 kali seminggu, P3: pemberian POC leri fermentasi 1 kali seminggu, P4: pemberian POC leri fermentasi 2 kali seminggu. Hasil penelitian ini diuji secara statistik dengan analisis ragam, dengan uji F; bila terdapat perbedaan nyata dilanjutkan dengan uji BNJ (Beda Nyata Jujur) pada taraf 0,05. Hasil penelitian menunjukkan perlakuan POC leri yang terbaik dalam meningkatkan pertumbuhan dan produksi selada adalah 25% POC leri fermentasi yang diberikan 2 kali seminggu, sebanyak 250 mL per tanaman selada. Secara tunggal perlakuan media tanam terbaik adalah M2 (tanah Ultisol+ 30 g biochar) dengan tinggi tanaman 25,80 cm dan jumlah daun 12, 83 helai; sedangkan perlakuan POC leri terbaik adalah P4 (POC leri fermentasi yang diberikan 2 kali seminggu), dengan tinggi tanaman 30,27 cm dan jumlah daun 14,42 helai. Berdasarkan berat basah tanaman, yang terbaik adalah pada perlakuan M2P4 (media tanam Ultisol + biochar dan POC leri fermentasi yang diberikan 2 kali seminggu), yaitu 185,99 g per tanaman. Kata kunci: cairan cucian beras, limbah rumah tangga, POC leri, selada